Agrivoltaics in Sweden - Antonini, Timothe; Da Corte Vecchino, Filippo; Melkersson, Emil; Merten, Tom; Pettersson, Nathalie (My University, 2025)
This report examines the integration of renewable energy into agriculture, focusing on agrivoltaic systems (APVs) that combine photovoltaic (PV) energy generation with farming. It compares Conventional Ground-Mounted Photovoltaics (CGMPVs) and Vertical Bifacial Photovoltaics (VBFPVs) to assess their economic viability and production potential. Additionally, it explores the implications and social acceptance of PV integration in Swedish agriculture, including land-use efficiency, food security, and market dynamics, offering insights for stakeholders seeking sustainable energy solutions in farming.